2011
DOI: 10.1186/1752-2897-5-8
|View full text |Cite
|
Sign up to set email alerts
|

HIV seroprevalence and its effect on outcome of moderate to severe burn injuries: A Ugandan experience

Abstract: BackgroundHIV infection in a patient with burn injuries complicates the care of both the patient and the treating burn team. This study was conducted to establish the prevalence of HIV among burn patients in our setting and to compare the outcome of these patients who are HIV positive with those who are HIV negative.MethodsThis was a prospective cohort study involving burn injury patients admitted to Mulago Hospital between November 2005 and February 2006. Patients were stratified into HIV positive (exposed) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Several studies have demonstrated the fact that HIV status does not impact the duration of inpatient stay . However, in disagreement, our results showed that HIV‐positive patients have a significantly longer hospital stay than HIV‐negative individuals.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Several studies have demonstrated the fact that HIV status does not impact the duration of inpatient stay . However, in disagreement, our results showed that HIV‐positive patients have a significantly longer hospital stay than HIV‐negative individuals.…”
Section: Discussioncontrasting
confidence: 82%
“…Another report from Malawi revealed an HIV prevalence of 31% among burn patients admitted during a 1-year study period with inpatient HIV prevalence from 30% to 70% (7). Additionally, another study from Uganda showed that the overall seroprevalence of HIV infection was 13⋅1% and 6⋅5% in HIV burn patients and the general population, respectively (9). In another study, Sheyo (10) reported 16% of their burn patients with positive HIV infection, while the prevalence of HIV in burn patients was the same as in the general population.…”
Section: Discussionmentioning
confidence: 98%
“…Insignificant changes in the level of CD16 (NK cells) population may induce apoptosis or activation induced cell death in mature lymphocytes. Therefore, it has to be taken into consideration that variable changes of CD19 + and CD16 + may contribute to the higher incidence of infection and sepsis in patients after burn injury, especially in cases with burns of >30% TBSA ( 26 , 32 , 35 ). Finally, the failure of peripheral blood lymphocytes to regulate the immune response is considered to be an important immunological and physiological consequence of major immunosuppression after thermal burn injury ( 1 , 4 , 36 - 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…This has placed stress on an already overstretched surgical work force. There has been an attempt to innovatively address this challenge by a number of strategies including task shifting, task sharing and increased training of surgical specialists [ 37 - 39 ].…”
Section: Introductionmentioning
confidence: 99%